Pengaruh Pengaruh Word of Mouth dan Kualitas Produk terhadap Keputusan Pembelian Konsumen (Studi Pada Livestream Tiktok Shop) - Riza Amalia Rifani; Saripah Aryanti; Syamsuriani Syamsuriani (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This research aims to determine the effect of word of mouth and product quality on purchase decision when the seller conducts a livestream on Tiktok shop. Multiple linear regression was used to test the hypothesis regarding the effect of Word of Mouth and Product Quality on purchase decision when the seller conducts a livestream on Tiktok shop. The results of hypothesis testing using t-test showed that Word of Mouth has a significant and negative effect on purchase decision, while Product Quality has a significant and positive effect on purchase decision. In addition, the independent variable that is dominant and has the greatest influence on purchase decision is product quality. These conclusions can serve as a reference for Tiktok shop sellers to improve purchase decisions by considering Word of Mouth and product quality.